2017
DOI: 10.1002/psp4.12181
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetics of Sulfadoxine and Pyrimethamine for Intermittent Preventive Treatment of Malaria During Pregnancy and After Delivery

Abstract: Sulfadoxine/pyrimethamine is recommended for intermittent preventative treatment of malaria during pregnancy. Data from 98 women during pregnancy and 77 after delivery in four African countries were analyzed using nonlinear mixed‐effects modeling to characterize the effects of pregnancy, postpartum duration, and other covariates such as body weight and hematocrit on sulfadoxine/pyrimethamine pharmacokinetic properties. During pregnancy, clearance increased 3‐fold for sulfadoxine but decreased by 18% for pyrime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
(59 reference statements)
4
28
0
Order By: Relevance
“…Potential confounders not included in the original modeling reduced, but did not eliminate, between‐site differences in pharmacokinetic parameters. For sulfadoxine, there was an overall threefold higher clearance during pregnancy vs. that after delivery, consistent with other available data2, 3, 4 and reflecting pregnancy‐associated physiological changes 1. Pyrimethamine clearance was, by contrast, 18% lower in pregnancy compared with the postpartum period, with a reduced area under the plasma concentration‐time curve (AUC) after delivery 1…”
Section: Figuresupporting
confidence: 87%
See 4 more Smart Citations
“…Potential confounders not included in the original modeling reduced, but did not eliminate, between‐site differences in pharmacokinetic parameters. For sulfadoxine, there was an overall threefold higher clearance during pregnancy vs. that after delivery, consistent with other available data2, 3, 4 and reflecting pregnancy‐associated physiological changes 1. Pyrimethamine clearance was, by contrast, 18% lower in pregnancy compared with the postpartum period, with a reduced area under the plasma concentration‐time curve (AUC) after delivery 1…”
Section: Figuresupporting
confidence: 87%
“…This suggests strongly that lactating women are not metabolically equivalent to nonpregnant women in the case of pyrimethamine. The reduced pyrimethamine clearance in pregnancy relative to that postpartum, as reported by de Kock et al .,1 does not, therefore, contradict other studies using nonpregnant women as the comparator group that showed increased pyrimethamine clearance and a lower AUC 3, 4…”
Section: Figuresupporting
confidence: 56%
See 3 more Smart Citations